2017
DOI: 10.1186/s13014-017-0930-9
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation for recurrent glioma- the NCI experience in tumor control, OAR toxicity and proposal of a novel prognostic scoring system

Abstract: Purpose/objectivesDespite mounting evidence for the use of re-irradiation (re-RT) in recurrent high grade glioma, optimal patient selection criteria for re-RT remain unknown. We present a novel scoring system based on radiobiology principles including target independent factors, the likelihood of target control, and the anticipated organ at risk (OAR) toxicity to allow for proper patient selection in the setting of recurrent glioma.Materials/methodsThirty one patients with recurrent glioma who received re-RT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…In the re-irradiation setting 42,43 , a smaller irradiated volume is preferable in terms of toxicity, while limiting treatment to contrast-enhancing lesions may lead to lower local control given the invasiveness of gliomas 14 . Accurately determining tumor spread is especially difficult in diffuse tumors, thus increasing the risk of local failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the re-irradiation setting 42,43 , a smaller irradiated volume is preferable in terms of toxicity, while limiting treatment to contrast-enhancing lesions may lead to lower local control given the invasiveness of gliomas 14 . Accurately determining tumor spread is especially difficult in diffuse tumors, thus increasing the risk of local failure.…”
Section: Discussionmentioning
confidence: 99%
“…14 median 30 Gy. 4 Furthermore, Scholtyssek et al reported on reirradiation applying median total doses of 36 Gy in single doses of 2-5 Gy. 15 In their cohort the median OS from the start of reirradiation was 7.7 months and the OS rates at 6and 12-months were 60% and 24%, respectively.…”
Section: Ion-beam Therapy Center Between October 2015 and December 20mentioning
confidence: 99%
“…15 In addition, Krauze et al did not observe any grade 3-5 AE during follow-up and reported mainly fatigue and alopecia as AE. 4 Fogh et al reported that none of their patients required hospitalization or surgery due to toxicity, while 1 patient developed grade 3 headaches. 14 However, even though treatment was generally well tolerated in our cohort and none of the patients was diagnosed with CTC grade 5 or 4 AE, 8 patients (27%) developed CTC grade 3 AE, requiring medical intervention.…”
Section: Ion-beam Therapy Center Between October 2015 and December 20mentioning
confidence: 99%
See 2 more Smart Citations